Perception of Impact of Formative Assessment on Professional Competences During Initial Teacher Training - Laura Cañadas; María Luisa Santos-Pastor; Patricia Ruiz Bravo (Universidad Autónoma de Baja California, 2021)
This study aims to assess the perception of the impact of innovative formative assessment experiences on competence development, and determine whether differences exist in competence development from one academic year to the next. A total of 40 university-level formative assessment experiences were taken into account, and a pre-validated questionnaire including three competence scales was completed by students before and after the formative assessment experience. Only 10 of the 45 competences studied exhibited no significant differences between the initial and final evaluation and no significant differences were recorded in perceived competence development between one academic year and the next.